TRENDS IN THE DEVELOPMENT OF UZBEKISTAN'S FINANCIAL MARKET AND DIRECTIONS FOR ENSURING ITS STABILITY (Ustozlar uchun, 2025)
This article analyzes the current state of Uzbekistan’s financial market, its structural composition, stages of development, and the main directions for ensuring its stability. The financial market plays an important role in stimulating investment processes, supporting economic growth rates, and efficiently reallocating financial resources. Using statistical, comparative, and analytical methods, the study examines the dynamics of key financial market indicators for the period 2018–2024. The analysis of international experience shows that improving institutional infrastructure, enhancing financial market efficiency, and strengthening investor confidence are essential for development. The article also proposes recommendations aimed at further improving the country's financial market stability.